LEGAL AND ETHICAL ASPECTS OF THE USE OF AI TECHNOLOGY IN THE WORLD OF EMPLOYMENT IN INDONESIA - Dikki Saputra Saragih; Parlindungan Purba; Micael Jeriko Damanik; Serfasius Siwanahono (PT. Radja Intercontinental Publishing, 2023)
Continuous advances in information technology, such as artificial intelligence (AI), open up new and exciting opportunities for shared value creation among economic actors. However, little is known about the mechanisms and processes of AI-enabled value co-creation. While scholars agree that AI technologies are significantly changing human activities and human capital, we currently do not have an adequate understanding of how humans and AI technologies interact in the co-creation of value. This is the central phenomenon investigated in this Journal. Specifically, using Service-Dominant Logic (S-DL) as a lens, this study investigates the activities, roles, and resources exchanged in AI-enabled value co-creation, using competitive intelligence creation as the research context. The analysis shows that the value co-creation process enabled by AI is a complex interaction between human and non-human actors performing one of six different roles either jointly or independently.